Geospatial techniques for sustainable human settlement design: a case study - Dawson-Ahmoah, Benedicta Nana Ansah (University of Mines and Technology, 2020)
In recent decades, the landscape of cities changed significantly because of rapid urban population growth, which has resulted in the struggle for space. This has been accompanied by many serious problems including inefficient use of land, encroachment of water bodies and forest, landuse specialisation, among others. It is therefore necessary to adopt strategies to address these problems through the designing communities. This study investigates the existing planning scheme of Mfuom community within the Upper Denkyira East Municipality in the central region of Ghana and proposed a sustainable planning scheme using geospatial techniques for the undeveloped portions to absorb the future population growth. The methods used include evaluation of existing planning scheme, household questionnaire administration, determination of proposed land area and plot sizes, proposal of community goals and objectives, the Analytical Hierarchy Process (AHP) and the Grey Relational Analysis (GRA). The evaluation of the existing planning scheme showed that, the current design was unsustainable since it was not exhibiting the component and principles of sustainable design. The total land area of the proposed settlement was calculated to be 303000m2 and plot sizes to be 450m2 using the medium residential density of the Ghana’s Planning and Zoning standards. The AHP was used in the selection of suitable urban design model for the study area by allocating weights to the various design models in order of suitability. A pairwise matrix was formed and then normalised. A consistency check was carried out and the consistency ratio was found to be 0.019 which is less than 0.1. Hence, the weights obtained for the types of the design models i.e., “Neighborhood Design model”, “Multi Nuclei Model”, “Sector Model” and “Concentric Model” were 0.51 (or 51%), 0.28 (or 28%), 0.13 (or 13%) and 0.08 (or 8%) respectively. Therefore, the neighbourhood design model was selected for the research. The GRA was then used in the selection of optimal site for some prominent landuses. Zone A, B, C, and D was selected for shopping area, Active recreational area and Health Centre, Police Post and Education respectively with their corresponding Grey Relational Grade (GRG) as 0.58, 0.54 and 0.81, 0.78 and 0.66. The final result of a settlement model designed proved that the design was sustainable and when implemented could absorb the future population growth and be free from current city spatial problems.
ix, 129; ill
Keywords: Geospatial issues; Urban planning; Land issues; Human geography